Seroconversión de la vacuna del virus del Papiloma Humano (HPV) en niñas del Colegio de Bachillerato Fiscomisional Nuestra Señora del Rosario de Catamayo en el periodo enero-junio 2016 - Pinzón Imaicela, Rosa María (2017)
Human Papillomavirus (HPV) is a disease that causes death worldwide; there are more than 100 strains of which two groups are established: those at low risk who produce genital warts and those at high risk that cause the cellular changes that sometimes generate cervical cancer and other cancers in the genitals and throat. With the theme: Seroconversion of the Human Papilloma Virus Vaccine (HPV) in girls from "Nuestra Señora del Rosario" High school in Catamayo in the period January-June 2016. In order to identify the seroconversion of human papillomavirus (HPV) vaccine in post-immunized girls, based on the definition of the age groups and time of immunization of the human papillomavirus (HPV) vaccine; in order to determine the seroconversion of the Human Papillomavirus (HPV) vaccine and to relate this Seroconversion to the post-immunization time of the girls. This study was a cross-sectional and descriptive study with a sample of 59 students aged 9, 10 and 12 years using biochemical analysis for bivalent Cervarix vaccine with HPV IgG; seroconversion is checked in the post-immunization time of 3 to 12 months of the aforementioned sample. Key Words: Seroconversion; HPV; Vaccine; post-immunization.